Inspiratory muscle training in patients with heart failure: A systematic review and meta-analysis - Li, Hui; Tao, Lingling; Huang, Yuewi; Li, Ziyang; Zhao, Jianrong (Frontiers in Cardiovascular Medicine, 2022)
Objective To explore the effect of inspiratory muscle training (IMT) on patients with heart failure and further explore the impact of IMT on patients with heart failure with preserved ejection fraction. Methods PubMed, EMBASE, Cochrane Library, CNKI, Wanfang and VIP databases were systematically searched. Randomized controlled trials of inspiratory muscle training in patients with heart failure were included. Revman 5.3 software was used to calculate the weighted mean difference (MD) of the combined effect size. The effects of IMT on the maximum oxygen uptake (peakVO2), maximum inspiratory pressure (PImax), ventilation efficiency (VE/VCO2), six-minute walking distance (6MWD), forced expiratory volume (FEV1), forced vital capacity (FVC) and quality of life in patients with heart failure were compared and analyzed. Results After systematic retrieval and screening, 17 studies were included in this study, and the quality of the included studies was good. The results showed that IMT could increase peakVO2 (MD 2.53; 95% CI 1. 54, 3. 51; P < 0.0001) and PImax (MD 17.25; 95% CI 13. 75, 20. 75; P < 0.00001); improve the VE/VCO2 (MD −4.22; 95% CI −6.78, −1.66; P = 0.001) and significantly improve the quality of life in patients with heart failure (MD −13.34; 95% CI −20.42, −6.26; P = 0.0002). However, the effect of IMT on 6MWD in patients with heart failure was not statistically significant (MD 74.45; 95% CI −12.88,161.79; P = 0.09), and the effect on lung function (FEV1 and FVC) was also not statistically significant (P = 0.08; P = 0.86). IMT had a more significant positive effect on peakVO2 (MD 2.98; 95% CI 1.63, 4.34; P < 0.0001) and quality of life (MD −14.52; 95% CI −18.53, −10.52; P < 0.00001) in patients with heart failure with preserved ejection fraction. Descriptive analysis suggested that IMT may positively affect dyspnoea in patients with heart failure. In addition, the choice of evaluation scale may affect the evaluation results of quality of life and dyspnoea. Conclusion IMT has a significant positive effect on respiratory status in patients with heart failure, but different dyspnoea and quality of life evaluation scales can affect the final evaluation results.